Agro-tourism and Rural Development in Nepal - Kaini, Malati (Patan Pragya, 2020)
In this paper more focus towards the rural areas development is given. Remarkable agricultural production is being gained by active involvement of rural population in available agricultural land. In this article the review is focused on agro-tourism. The main purpose of this paper is to know the situation of rural areas in the context of agro-tourism. Tanahun district has been selected for this review study where 1.22% of the total population is working within 1.05% agricultural land of the country. Agro tourism allows close link of outsiders with the inhabitants of rural villages where small farmers have been involved in traditional way of agriculture. This type of integration surely helps for running home stay and employing rural youth. Thus, agro-tourism can become the best option for socio-economic promotion of rural areas in the district. This type of development model will certainly be helpful for the development of rural areas in other Provinces.